Induction of active demethylation and 5hmC formation by 5-azacytidine is TET2 dependent and suggests new treatment strategies against hepatocellular carcinoma - Sajadian, Sahar Olsadat; Dooley, Steven (Clinical epigenetics, 2015)
Background: Global deregulation of DNA methylation is one of the crucial causes of hepato cellular carcinoma (HCC). It has been reported that the anti-cancer drug 5-azacytidine (5-AZA) mediates the activation of tumor suppressor genes through passive demethylation by inhibiting DNMT1. Recent evidence suggests that active demethylation which is mediated by ten-eleven translocation (TET) proteins may also be an important step to control global methylation. However, there exists a controversial discussion in which TET proteins are involved in the demethylation process in HCC. Therefore, we firstly wanted to identify which of the TETs are involved in demethylation and later to study whether or not 5-AZA could trigger the TET-dependent active demethylation process in HCC. HCC cell lines (Huh-7, HLE, HLF), primary human hepatocytes (hHeps), and tissues from both healthy (55 patients) and HCC patients (55 patients) were included in this study; mRNA levels of isocitrate dehydrogenase (IDH1, 2) and TETs (TET1–3) were studied via qPCR and confirmed by Western blot. The expression of 5hmC/5mC was determined by immunohistochemistry in human HCC tissues and the corresponding adjacent healthy liver. HCC cell lines were stimulated with 5-AZA (0–20 μM) and viability (Resazurin conversion), toxicity (LDH release), proliferation (PCNA), and 5hmC/5mC distribution were assessed. In addition, knockdown experiments on TET proteins in HCC cell lines using short interference RNAs (siRNAs), in the presence and absence of 5-AZA, were performed. Results: Our data applying qPCR, immunofluorescence, and Western blotting clearly show that TET2 and TET3 but not TET1 were significantly decreased in HCC tissue and different HCC cell lines compared to non-tumor liver tissues and hHeps. In addition, we show here for the first time applying knockdown experiments that 5-AZA is able to trigger an active TET2-dependent demethylation process with concomitant significant changes in 5hmC/5mC in HCC cell lines and hHeps. Conclusions: Our data clearly show that the expression and activity of TET2 and TET3 proteins but not TET1 are impaired in hepatocellular carcinoma leading to the reduction of 5hmC in HCCs. Furthermore, this study identified a novel function of 5-azacytidine in promoting a TET-mediated generation of 5hmC suggesting that the availability of 5-AZA in cancer cells will have various effects on different epigenetic targets. These findings may open new therapeutic strategies for epigenetic drugs to treat HCC.